HER2-targeted therapy influences CTC status in metastatic breast cancer - Deutsch, Thomas M.; Riethdorf, Sabine; Fremd, Carlo; Feißt, Manuel; Nees, Juliane; Fischer, Chiara; Hartkopf, Andreas; Pantel, Klaus; Trumpp, Andreas; Schütz, Florian; Schneeweiss, Andreas; Wallwiener, Markus (Breast cancer research and treatment, 2020)
PURPOSE: As an independent, negative-prognostic biomarker for progression-free survival (PFS) and overall survival (OS), circulating tumor cells (CTCs) constitute a promising component for developing a liquid biopsy for patients with metastatic breast cancer (MBC). The effects of HER2-targeted therapy such as trastuzumab, pertuzumab, T-DM1, and lapatinib on CTC status and longitudinal enumeration were assessed in this trial. - METHODS: CTC status of 264 patients with MBC was analyzed prior to and after 4 weeks of a new line of palliative systemic therapy. CTCs were assessed using CellSearch®. Three groups were compared: patients with HER2-positive MBC receiving ongoing HER2-targeted therapy (n = 28), patients with de novo HER2-positive MBC and no HER2-targeted therapy in the last 12 months prior to enrollment and start of HER2-targeted therapy (n = 15), and patients with HER2-nonamplified disease and no HER2-targeted therapy (n = 212). - RESULTS: Positive CTC status (≥ 5 CTC/7.5 ml blood) at enrollment was observed in the 3 groups for 17.9, 46.7, and 46.2% (p = 0.02) of patients, respectively. At least one CTC/7.5 ml was seen in 28.6, 53.3, and 67.0% (p < 0.001) of these patients. Furthermore, 3.6, 40.0, and 3.3% (p < 0.001) of the patients had at least one HER2-positive CTC. After 4 weeks of therapy 7.1, 0.0, and 31.1% (p = 0.001) of patients had still a positive CTC status (≥ 5 CTC/7.5 ml blood). At least one CTC/7.5 ml was still observed in 25.0, 20.0, and 50.5% (p = 0.004) of the patients. Furthermore, 7.1, 0.0, and 1.9% (p = 0.187) had at least one HER2-positive CTC. After 3 months of therapy, 35.7, 20.0, and 28.3% (p = 0.536) showed disease progression. - CONCLUSIONS: HER2-targeted therapy seems to reduce the overall CTC count in patients with MBC. This should be taken into account when CTC status is used as an indicator for aggressive or indolent metastatic tumor disease.
Gesehen am 20.10.2021